Bilateral maxillary palatal talon cusps in deciduous central incisors. Issue 2 (12th February 2019) - AlHumaid, Jehan
Abstract : 'Talon cusp' is a developmental dental disturbance characterised by a cuspal projection in the cingulum area or cementoenamel junction, with normal enamel and dentin containing varying degrees of pulp tissue. The prevalence of talon cusp varies with race, age and the criteria used for diagnosis. It has been reported in the maxillary and mandibular arches of both the deciduous and permanent dentitions. The prevalence of the talon cusp in the deciduous dentition is reported to be 2.1% in Saudi Arabian subjects. The purpose of this paper is to report the rare bilateral presence of talon cusps on the deciduous maxillary central incisors of a 4-year-old female patient with a family history of consanguineous marriage.